BEKERJA PADA ORGANISASI YANG TIDAK SEHAT: PELUANG ATAU KUTUKAN BAGI KARYAWAN? - Arundati Shinta; Dian Yudhawati; Lusia Gayatri (JURNAL SPIRITS, 2012)
ABSTRACTObjective of this paper is to explain behavior alternatives for employees ,'ho have job dissatisfaction. When accomplishing job task, the religious employees will certainly practice one of their code of belief that working is a kind of religious service. They work vigorously as if tomorrow will he the end of the world. When their organization is going to collapse, the religious employees experience cognitive dissonance (hopes and realities are unsynchronized). They have difficulties in practicing that working is a kind of religious service.There are four behavior alternatives in order to lessening cognitive dissonance i.e. exit or leaving organization (active destructive), neglect (passive destructive), loyal (passive constructive), and voice (active constructive). The voice alternative is the most appropriate behavior for the religious employees, but it less likely to give maximal improvement either for employees or organization.The suggested alternative in this essay is the adapted negotiation alternative which employees have to change and improve themselves. Through improving themselves, they have opportunity either to perform high quality job accomplishment or supporting friends to accomplish their tasks. The adapted negotiation is applying religious service that giving firstly, then we will receive abundance i.e. having creative ability in job accomplishment, ability to act positively in chaos situation, and having good mental health. Changing ourselves is really difficult. However there are precious words which could be our guidance that the crucial factor in achieving success is not the obstacle existence but our unconstructive attitude in facing that obstacle.Key words: Job dissatisfaction, religious service, adapted negotiation